URGENSI PENILAIAN HASIL BELAJAR BERBASIS KELAS MATA PELAJARAN IPS DI MADRASAH TSANAWIYAH - Ramli Abdullah (UIN AR-RANIRY, 2015)
Class-based assessment is a process of collecting, reporting, and using student learning information of the measuring activities analyzed to identify student achievement in performing learning tasks, as well as activities undertaken in order to obtain and streamline information on learning outcomes Students during or after experiencing the learning experience. Assessment of learning outcomes whose purpose is to know the mastery of students in mastering basic competencies, and from the assessment activities can be known basic competencies, materials, or indicators that have not reached completeness. While the learning outcome is a picture of the progress or development of students, from the very beginning of the education program until the end of their educational program. By assessing the learning outcomes, teachers will benefit greatly to make improvements to future learning programs.